NILAI-NILAI PENDIDIKAN DALAM TOR-TOR NAPOSO NAULI BULUNG - Meiliza Hijrati; Siti Rahmah (Universitas Negeri Medan, 2018)
ABSTRACT This study aims to describe Educational Values in Tor-Tor Naposo Nauli Bulung. Theories used in this study include value theory and educational theory. The method used in this research is descriptive qualitative method. The population of this research are South Tapanuli people in Mabar Hilir and Deli Serdang, and the sample of this research are 3 South Tapanuli people in Deli Serdang and Mabar Hilir. In the discussion of this study as for the focus of my research is using the theory of religious values according to Abdul (2012: 129) and moral values according to Sutardjo (2011: 54). This study aims to describe the educational values in Tor-Tor Naposo Nauli Bulung. Data collection in this research is done by observation method, interview, documentation, and analysis technique. This study discusses the explanation of the values of education contained in Tor-Tor Naposo Nauli Bulung for dancers and the public to know that in a dance there are also good values that can be a positive value in everyday life and can be used as material teachers for learners. The results of the research can be seen that in Tor-Tor Naposo Nauli Bulung, contained the values of education in which viewed from the pattern of motion, fashion, music, and rules. The values are peeled through religious values and moral values which can then be used as a source of information to the community and the dancers that there are values that can be used as learning can also be used as teacher material for learners. Keyword: Value, Education, Religious Value, Moral Value, Tor-Tor Naposo Nauli Bulung.